Halogen-modified bimetallic phosphide as well as preparation method and application thereof
By preparing halogen-modified bimetallic phosphides on a nickel substrate, the problems of high cost of precious metal catalysts and unsatisfactory bimetallic phosphides are solved, and efficient full electrolytic hydrolysis and excellent catalytic activity are achieved.
Patent Information
- Application Number
- CN202411014193.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-04-29
AI Technical Summary
In the prior art, precious metal catalysts are expensive and limited in reserves, which limit the industrial application of electrolytic water catalysts. Especially in HER and OER reactions, the OER performance of bimetallic phosphides is not ideal.
Halogen-modified bimetallic phosphides such as CoMnP-Cl and CoMnP-Br are prepared by hydrothermal reaction and high temperature phosphating on a nickel substrate, which exhibit excellent properties in the catalytic activity of HER and OER.
It realizes efficient and complete water dissolution of a dual-function catalyst, has excellent HER and OER catalytic activity, is low in cost, rich in resources, and has good catalytic efficiency and stability.
Smart Images

Figure HDA0004965235840000011 
Figure HDA0004965235840000012 
Figure HDA0004965235840000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrolytic water catalysis, and in particular relates to a halogen-modified bimetallic phosphide and a preparation method and application thereof. Background Art
[0002] Developing green new energy to replace traditional fossil energy and achieve a low-carbon green transition is one of the most challenging tasks currently. It can also solve many problems such as ecological imbalance caused by environmental problems. Hydrogen energy is the best green energy, and the development of environmentally friendly hydrogen production methods is urgent. The most effective and environmentally friendly method for producing hydrogen is to split water using electrochemical methods, that is, to induce water molecules to decompose into hydrogen and oxygen by applying voltage. However, the HER (hydrogen evolution reaction at the cathode) electrocatalysts that can currently achieve the best performance are precious metal platinum (Pt)-based catalysts, and the most advanced OER (oxygen evolution reaction at the anode) electrocatalysts are electrocatalysts such as precious metal oxides (IrO2, RuO2). However, the high price and low abundance of precious metals greatly limit their application in the industrial market. Therefore, exploring low-cost, abundant, and high-performance HER and OER electrocatalysts to replace precious metals is of great significance to the development of OWS.
[0003] In recent years, transition metals and their compounds have been extensively studied, with numerous reports on highly efficient transition metal oxides, nitrides, sulfides, phosphides, and borides for water electrolysis. Transition metal phosphides (TMPs) are considered promising catalysts for water electrolysis due to their excellent conductivity and unique electronic structure. Monometallic phosphides, such as CoP, Ni2P, and FeP, exhibit excellent HER performance due to their structural similarity to hydrogenases. However, they also have some drawbacks. Monometallic phosphides lack abundant active sites and are easily corroded in high-potential, strong alkaline environments. In contrast, bimetallic phosphides not only enhance the metallic properties, thereby improving their intrinsic conductivity, but also provide a favorable surface electronic structure and coordination environment, thereby enhancing catalytic reaction activity. They can also induce changes in the active sites, making the hydrogen / oxygen adsorption process on the catalyst surface thermodynamically more efficient. It can be seen that bimetallic phosphides have lower overpotential and better catalytic activity than monometallic phosphides. However, if they are used as bifunctional catalysts to achieve efficient complete water splitting, the OER performance of transition metal phosphides is not ideal. Therefore, how to use reasonable methods to modify TMPs is the focus of current research. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a halogen-modified bimetallic phosphide and its preparation method and application in response to the deficiencies of the prior art. The halogen-modified bimetallic phosphide provided by the present invention has excellent HER and OER catalytic activity.
[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0006] A halogen-modified bimetallic phosphide comprises a nickel substrate and a halogen-modified bimetallic phosphide grown on the nickel substrate, which is doped with halogen, wherein the halogen is chlorine or bromine, and contains a phosphide of metallic cobalt and nickel, and has bonding between metallic cobalt and manganese as well as phosphorus and oxygen.
[0007] According to the above scheme, the chlorine-modified bimetallic phosphide CoMnP-Cl is a nanoflower structure formed by rotating nanorods with tapered tips, which is evenly and densely distributed on the nickel substrate, exposing more electrochemically active surface area.
[0008] According to the above scheme, the diameter of the nanorods in the chlorine-modified bimetallic phosphide CoMnP-Cl is about 80-300 nm, and the surface of the nanorods is smooth.
[0009] According to the above scheme, the bromine-modified bimetallic phosphide CoMnP-Br is a nano-spherical structure composed of nanorods.
[0010] According to the above scheme, the halogen content is 0.1-1 wt%.
[0011] According to the above solution, the nickel substrate includes nickel foam, nickel mesh, and nickel felt.
[0012] The present invention also provides a method for preparing a halogen-modified bimetallic phosphide, comprising pre-treating a nickel base material as a base, using a cobalt source material and a manganese source material, performing a hydrothermal reaction in the presence of NH4X, where X is Cl or Br, and (NH2)2CO to deposit a halogen-modified cobalt-manganese precursor on the base; and using NaH2PO2 to prepare the halogen-modified bimetallic phosphide by a high-temperature phosphating method.
[0013] According to the above scheme, the pretreatment is: cutting the nickel base material, then ultrasonically cleaning the cut nickel base material with hydrochloric acid, anhydrous ethanol and deionized water in sequence, taking it out and drying it to obtain a pretreated base.
[0014] In the above scheme, the temperature of the hydrothermal reaction is 100-200° C., and the time is 4-20 hours.
[0015] In the above scheme, the calcination temperature is 300-450° C. and the calcination time is 0.5-3 hours.
[0016] In the above scheme, the high-temperature phosphating method is: placing the halogen-modified cobalt-manganese precursor in the downstream position of a tube furnace, placing NaH2PO2 in the upstream position of the tube furnace, and calcining under an inert atmosphere to prepare a halogen-modified bimetallic phosphide.
[0017] The present invention also claims protection for the halogen-modified bimetallic phosphide prepared by the above method.
[0018] The halogen-modified bimetallic phosphide can be used as a bifunctional catalyst in the electrocatalytic oxygen evolution and / or electrocatalytic hydrogen evolution.
[0019] Application of the above-mentioned halogen-modified bimetallic phosphide in electrocatalytic water splitting.
[0020] Compared with the existing technology, the beneficial effects of the present invention are:
[0021] (1) The present invention provides a halogen-modified bimetallic phosphide having excellent HER and OER catalytic activity, which can be used as a bifunctional catalyst with excellent electrocatalytic oxygen evolution and hydrogen evolution performance, and has good catalytic efficiency and stability.
[0022] (2) The present invention provides a method for preparing a halogen-modified bimetallic phosphide, wherein a nickel base material is used as a base material, and a halogen-modified bimetallic phosphide is in situ grown on the base material by a one-step hydrothermal method and a one-step high-temperature phosphating method. The prepared halogen-modified bimetallic phosphide has excellent HER and OER catalytic activity. The introduction of halogen atoms Cl or Br optimizes the morphological characteristics of the bimetallic phosphide, and the morphological structure can expose a larger active specific surface area, thereby providing more active sites.
[0023] (3) The present invention provides a method for preparing a halogen-modified bimetallic phosphide. The raw materials used in this method are low in cost and abundant in resources compared to precious metal materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Scanning electron microscope (SEM) images of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1;
[0025] Figure 2 This is a transmission electron microscope (TEM) image of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1 of the present invention;
[0026] Figure 3 EDX spectrum and element ratio diagram of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1 of the present invention.
[0027] Figure 4 X-ray diffraction (XRD) pattern of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1 of the present invention (a) and Raman spectrum (Raman) pattern of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1 and the bimetallic phosphide CoMnP sample prepared in Comparative Example 1 (b).
[0028] Figure 5 X-ray photoelectron spectroscopy (XPS) of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1 of the present invention and the bimetallic phosphide CoMnP sample prepared in Comparative Example 1.
[0029] Figure 6 This is a graph showing the OER performance test of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1.
[0030] Figure 7 The halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1 were tested for OER performance at scan rates of 20, 40, 60, 80, 100, and 120 mV s -1 CV curve when .
[0031] Figure 8 Fitting curves (a) of capacitance current and scan rate of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1 in the OER performance test, and LSV curves (b) normalized by electrochemically active specific surface area.
[0032] Figure 9 HER performance test diagram of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1.
[0033] Figure 10 The HER performance of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1 was tested at scan rates of 20, 40, 60, 80, 100, and 120 mV s -1 CV curve when .
[0034] Figure 11 Fitting curves (a) of capacitance current and scan rate of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1 in the HER performance test, and LSV curves (b) normalized by electrochemically active specific surface area.
[0035] Figure 12 This is a test chart of the full water splitting performance of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 of the present invention and the bimetallic phosphide sample prepared in Comparative Example 1.
[0036] Figure 13 This is a comparison of the full water splitting performance curves of CoMnP-Cl catalysts grown on different substrates in the AEM electrolyzer.
[0037] Figure 14 The stability of AEM electrolysis cell operation of CoMnP-Cl catalyst grown on nickel felt substrate. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] In a specific embodiment, the anhydrous ethanol, Co(NO3)2·6H2O, Mn(NO3)2·4H2O, (NH2)2CO, NH4Cl, NH4F, NH4Br, NH4I, and NaH2PO2 used are all analytically pure and purchased from Sinopharm Chemical Reagent Co., Ltd.; the nickel foam thickness is 1.5 mm and purchased from Sinopharm Chemical Reagent Co., Ltd.; the nickel mesh thickness is 0.2 mm and purchased from Sinopharm Chemical Reagent Co., Ltd.; the nickel felt thickness is 0.5 mm and purchased from Maipengchen Electronic Technology Co., Ltd.; and hydrochloric acid is purchased from Sinopharm Chemical Reagent Co., Ltd.
[0040] Example 1
[0041] A method for preparing a halogen-modified bimetallic phosphide comprises the following steps:
[0042] (1) Substrate pretreatment: The nickel foam was cut into 2 cm × 5 cm square pieces, and then ultrasonically cleaned with 37% hydrochloric acid (3M), anhydrous ethanol, and deionized water for 15 minutes, and then dried to obtain a pretreated substrate;
[0043] (2) Performing a hydrothermal reaction: Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4Cl and (NH2)2CO were dissolved in 60 mL of deionized water in sequence, and stirred thoroughly to dissolve all the reagents to obtain a clear solution, wherein the concentrations of Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4Cl and (NH2)2CO in the clear solution were all 0.1 M; the clear solution was placed in a 100 mL polytetrafluoroethylene hydrothermal reactor, the pretreated substrate was tilted against the edge of the hydrothermal reactor, and then the hydrothermal reactor was sealed in a steel bottle and placed in an oven, the temperature was set to 120°C and heated for 6 hours for a hydrothermal reaction, and after the reaction was completed, the deionized water was repeatedly rinsed and dried to obtain a chlorine-modified cobalt-manganese precursor;
[0044] (3) Performing high-temperature phosphating reaction: placing the chlorine-modified cobalt-manganese precursor in a porcelain boat and placing it in the downstream position of the tube furnace, placing 1 g of NaH2PO2 in a porcelain boat and placing it in the upstream position of the tube furnace, and calcining at 350 ° C for 2 hours under a nitrogen atmosphere to obtain a chlorine-modified bimetallic phosphide.
[0045] Example 2
[0046] A method for preparing a halogen-modified bimetallic phosphide comprises the following steps:
[0047] (1) Pretreatment of the substrate: The nickel foam was cut into 2 cm × 5 cm square pieces, and then ultrasonically cleaned with low concentration hydrochloric acid (3M), anhydrous ethanol, and deionized water for 15 minutes, and then dried to obtain the pretreated substrate;
[0048] (2) Performing a hydrothermal reaction: Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4F and (NH2)2CO were dissolved in 60 mL of deionized water in sequence, and stirred thoroughly to dissolve all the reagents to obtain a clear solution, wherein the concentrations of Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4F and (NH2)2CO in the clear solution were all 0.1 M; the clear solution was placed in a 100 mL polytetrafluoroethylene hydrothermal reactor, the pretreated substrate was tilted against the edge of the hydrothermal reactor, and then the hydrothermal reactor was sealed in a steel bottle and placed in an oven, the temperature was set to 120°C and heated for 6 hours to perform a hydrothermal reaction, and after the reaction was completed, the deionized water was repeatedly rinsed and dried to obtain a fluorine-modified cobalt-manganese precursor;
[0049] (3) Performing a high-temperature phosphating reaction: placing the fluorine-modified cobalt-manganese precursor in a porcelain boat and placing it in the downstream position of a tube furnace, placing 1 g of NaH2PO2 in a porcelain boat and placing it in the upstream position of the tube furnace, and calcining at 350 ° C for 2 hours under a nitrogen atmosphere to obtain a fluorine-modified bimetallic phosphide.
[0050] Example 3
[0051] A method for preparing a halogen-modified bimetallic phosphide comprises the following steps:
[0052] (1) Pretreatment of the substrate: The nickel foam was cut into 2 cm × 5 cm square pieces, and then ultrasonically cleaned with low concentration hydrochloric acid (3M), anhydrous ethanol, and deionized water for 15 minutes, and then dried to obtain the pretreated substrate;
[0053] (2) Performing a hydrothermal reaction: Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4Br and (NH2)2CO were dissolved in 60 mL of deionized water in sequence, and stirred thoroughly to completely dissolve all the reagents to obtain a clear solution, wherein the concentrations of Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4Br and (NH2)2CO in the clear solution were all 0.1 M; the clear solution was placed in a 100 mL polytetrafluoroethylene hydrothermal reactor, the pretreated substrate was tilted against the edge of the hydrothermal reactor, and then the hydrothermal reactor was sealed in a steel bottle and placed in an oven, the temperature was set to 120°C and heated for 6 hours to perform a hydrothermal reaction, and after the reaction was completed, the deionized water was repeatedly rinsed and dried to obtain a bromine-modified cobalt-manganese precursor;
[0054] (3) Perform high-temperature phosphating reaction: Place the bromine-modified cobalt-manganese precursor in a porcelain boat and place it in the downstream position of the tube furnace. Place 1 g of NaH2PO2 in a porcelain boat and place it in the upstream position of the tube furnace. Calcinate at 350°C for 2 hours under a nitrogen atmosphere to obtain a bromine-modified bimetallic phosphide.
[0055] Example 4
[0056] A method for preparing a halogen-modified bimetallic phosphide comprises the following steps:
[0057] (1) Pretreatment of the substrate: The nickel foam was cut into 2 cm × 5 cm square pieces, and then ultrasonically cleaned with low concentration hydrochloric acid (3M), anhydrous ethanol, and deionized water for 15 minutes, and then dried to obtain the pretreated substrate;
[0058] (2) Performing a hydrothermal reaction: Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4I and (NH2)2CO were dissolved in 60 mL of deionized water in sequence, and stirred thoroughly to completely dissolve all the reagents to obtain a clear solution, wherein the concentrations of Co(NO3)2·6H2O, Mn(NO3)2·4H2O, NH4I and (NH2)2CO in the clear solution were all 0.1 M; the clear solution was placed in a 100 mL polytetrafluoroethylene hydrothermal reactor, the pretreated substrate was tilted against the edge of the hydrothermal reactor, and then the hydrothermal reactor was sealed in a steel bottle and placed in an oven, the temperature was set to 120°C and heated for 6 hours to perform a hydrothermal reaction, and after the reaction was completed, the deionized water was repeatedly rinsed and dried to obtain an iodine-modified cobalt-manganese precursor;
[0059] (3) Performing a high-temperature phosphating reaction: placing the iodine-modified cobalt-manganese precursor in a porcelain boat and placing it in the downstream position of a tube furnace, placing 1 g of NaH2PO2 in a porcelain boat and placing it in the upstream position of the tube furnace, and calcining at 350 ° C for 2 hours under a nitrogen atmosphere to obtain an iodine-modified bimetallic phosphide.
[0060] Example 5
[0061] The nickel substrate is replaced with nickel mesh or nickel felt to prepare halogen-modified bimetallic phosphide.
[0062] Comparative Example 1
[0063] In step (2) of Comparative Example 1, no NH4Cl was added.
[0064] Test Example 1
[0065] This test is used to illustrate the microscopic morphology of the halogen-modified bimetallic phosphide material of the present invention.
[0066] Figure 1 The scanning electron microscope (SEM) images of the halogen-modified bimetallic phosphide samples prepared in Examples 1-4 and the bimetallic phosphide sample prepared in Comparative Example 1 are shown. Figure 1 It can be seen that the fluorine-modified bimetallic phosphide CoMnP-F prepared in Example 2 exhibits a tightly stacked nanoblock structure; the chlorine-modified bimetallic phosphide CoMnP-Cl prepared in Example 1 shows a nanoflower structure obtained by rotating nanorods with tapered tips, which is evenly distributed and dense on the nickel foam substrate, exposing more electrochemically active surface area; the bromine-modified bimetallic phosphide CoMnP-Br prepared in Example 3 exhibits a nanospherical structure composed of nanorods, and the nanorods are adhered to each other, exposing less electrochemically active surface area to a certain extent; the iodine-modified bimetallic phosphide CoMnP-I prepared in Example 4 shows a morphological feature of coexistence of disordered straw-like structures and nanospherical structures; the bimetallic phosphide CoMnP sample without any halogen modification prepared in Comparative Example 1 presents a nanorod array, and the material only exhibits a single nanorod-like structure and is arranged in a disordered manner.
[0067] Test Example 2
[0068] This test is used to illustrate the microstructure and element distribution of the halogen-modified bimetallic phosphide material of the present invention.
[0069] Figure 2 This is a transmission electron microscope (TEM) image of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1, wherein: Figure 2 (a) and (b) show the TEM images of CoMnP-Cl samples at different magnifications. It can be seen that CoMnP-Cl exhibits a nanorod-like structure with a pointed cone. The cross-sectional width of the nanorod is about 200nm. The surface of the nanorod in the image is relatively smooth, which is conducive to the release of bubbles and the penetration of electrolyte. At the same time, the pointed cone nanorod exposes more active surface area. Figure 2(c) High-resolution transmission electron microscopy (HRTEM) images show the presence of clear lattice fringes on the CoMnP-Cl nanorods, where the fringes have spacings of 0.29 nm and 0.33 nm, corresponding to the (002) and (102) planes of Co2P, respectively, proving the presence of transition metal phosphides in the material. Figure 2 (di) EDS element mapping images show that the elements (Co, Mn, P and Cl) of CoMnP-Cl material are evenly distributed. The proportion of each element is tested, such as Figure 3 The EDX spectrum and element ratio of the CoMnP-Cl material are shown, wherein the doping amount of chlorine atoms is 0.38at%.
[0070] Test Example 3
[0071] This test is used to illustrate the phase structure of the halogen-modified bimetallic phosphide material of the present invention.
[0072] Figure 4 (a) is the X-ray diffraction (XRD) pattern of the chlorine-modified bimetallic phosphide CoMnP-Cl sample prepared in Example 1, Figure 4 (b) is the Raman spectrum of the chlorine-modified double metal phosphide CoMnP-Cl sample prepared in Example 1 and the double metal phosphide CoMnP sample prepared in Comparative Example 1. Figure 4 (a) It can be seen that there are three strong diffraction peaks (44.51°, 51.86°, 76.32°), which are the characteristic peaks of the nickel foam substrate (PDF#4-850), while the other several weaker diffraction peaks can be attributed to Ni 12 The characteristic peaks of P5 (PDF#65-1623) and Co2P (PDF#65-2380), combined with the TEM analysis shown above, clearly show the lattice fringes of Co2P, proving the presence of nickel phosphide and cobalt phosphide in the phase structure analysis of the material. Figure 4 (b) It can be seen that the Raman spectra of the two materials are slightly different, with the peaks at 515-575 cm -1 The broad peak at 720 cm-1 can be attributed to the stretching vibration mode of the Mn-O bond. -1 The characteristic peaks at 190 and 291 cm -1 The characteristic peaks at , correspond to the vibration mode of Co-O and the E g Symmetrical vibration scattering, the other at 670cm -1 The characteristic peak at corresponds to the A 1gThe XRD and Raman phase characterization analyses above demonstrate the formation of transition metal phosphides in the sample and the presence of metal-oxygen bonding, with the chlorine atom exhibiting no obvious characteristic peak signals due to its low doping level.
[0073] Figure 5 X-ray photoelectron spectroscopy (XPS) of the chlorine-modified double metal phosphide CoMnP-Cl sample prepared in Example 1 and the double metal phosphide CoMnP sample prepared in Comparative Example 1. Figure 5 (a) It can be seen that a pair of spin-orbit dipoles (Co 2p 1 / 2 and Co 2p 3 / 2 ) and two satellite peaks (abbreviated as “Sat.”). After deconvolution, Co 2p 3 / 2 There are two signal peaks in the characteristic peak, with binding energies of around 781.98 and 784.68 eV, corresponding to Co 3+ and Co 2+ species, and the corresponding Co 2p 1 / 2 The characteristic peak is located at 798.28eV, and the two characteristic peaks at 802.78 and 787.48eV are satellite peaks. 3+ / Co 2+ The peak area ratio of Co in the Cl-modified CoMnP sample is about 2.2. 3+ / Co 2+ The peak area ratio of increased to 5.0, indicating that the introduction of Cl increases the valence of Co species. From a theoretical point of view, high-valence metal sites dominate the OER activity of transition metal compounds, inducing the relevant cobalt sites to undergo pre-oxidation (easier to form active intermediates) and have better oxygen species (hydroxyl and oxygen) adsorption / desorption capabilities, which is beneficial to the OER reaction. Figure 5 (b) It can be seen that a pair of dipoles (Mn 2p 1 / 2 and Mn 2p 3 / 2 ) and a satellite peak. After deconvolution, Mn 2p 3 / 2 There are two signal peaks in the characteristic peak, with binding energies of around 641.78 and 643.58 eV, corresponding to Mn 3+ and Mn 4+ species, which can be attributed to surface oxides, while Mn 2p 1 / 2 There are also two main peaks in the energy level region, with binding energies of around 653.68 and 654.88 eV, which also correspond to Mn 3+ and Mn 4+ species, and the characteristic peak at 647.18 eV is a satellite peak. In the CoMnP sample without chlorine modification, Mn4+ / Mn 3+ The peak area ratio of the Cl-modified CoMnP sample is about 0.69, but the Mn 4+ / Mn 3+ The peak area ratio of α decreased to 0.43, indicating that the introduction of Cl reduced the valence of Mn species. Figure 5 (c) It can be seen that the characteristic peak with a binding energy of 134.48 eV in the CoMnP-Cl sample corresponds to the spin-orbit PO bond, and there is a weaker characteristic peak with a binding energy of around 129.88 eV, which corresponds to the MP bond. The existence of PO is because the surface of the transition metal phosphide is easily oxidized in the air, thereby forming an active phase PO suitable for OER. In addition, the surface layer containing PO also serves as a passivation layer of the material, effectively preventing TMPs from further dissolving in the electrolyte. Compared with the control sample, the PO bond in the non-chlorine-modified CoMnP sample has a binding energy of 134.39 eV, indicating that the introduction of Cl causes the characteristic peak corresponding to the PO bond to shift, which may change the valence state of P to a certain extent. From Figure 5 (d) It can be seen that Cl 2p appears in the Cl-modified CoMnP material. 1 / 2 The characteristic peak of the CoMnP-Cl electrode was detected, and two signal peaks appeared after deconvolution, with binding energies of approximately 200.38 and 198.78 eV, indicating that Cl was successfully introduced into the CoMnP-Cl material and that its introduction effectively optimized the electronic structure of the CoMnP electrode material. The XPS analysis above shows that the successful introduction of the non-metallic element Cl slightly changes the valence state of each element, promoting electron transfer to a certain extent, thereby facilitating the HER and OER reactions.
[0074] Test Example 4
[0075] This test is used to illustrate the OER performance and stability of the halogen-modified bimetallic phosphide material of the present invention.
[0076] The performance of the samples was tested and analyzed in an electrochemical workstation. At room temperature, the chlorine-modified bimetallic phosphide prepared in Example 1, the bromine-modified bimetallic phosphide prepared in Example 3, the fluorine-modified bimetallic phosphide prepared in Example 2, the iodine-modified bimetallic phosphide prepared in Example 4, and the bimetallic phosphide sample prepared in Comparative Example 1 were assembled as catalysts in a three-electrode system to evaluate their OER performance. The electrolyte environment provided was an alkaline electrolyte (1MKOH). A comprehensive analysis of the test results showed that the cobalt manganese phosphide can significantly improve the OER catalytic performance after being modified with chlorine and bromine. The specific results are as follows: First, cyclic voltammetry scanning (CV) was performed on different catalysts to activate the materials. After the sample activation was stable, a linear sweep voltammetry (LSV) test was performed. The test results are as follows: Figure 6As shown in (a), it can be seen that Cl-modified CoMnP exhibits the best catalytic performance at 10 mA cm -2 The overpotential is only 223mV at a current density of 1000 nm, which is better than that of commercial catalyst IrO2 (270mV@10mA cm -2 ). Figure 6 (b) Different current densities (10, 100 and 300 mA cm -2 ) under different overpotentials of catalysts. It can be seen that the Cl-modified CoMnP material has a high overpotential at 300 mA cm -2 It also has a low overpotential at a larger current density, requiring only an overpotential of 371mV. Figure 6 (c) is the Tafel slope of different catalysts. It can be seen that the Tafel slope of Cl-modified CoMnP material is the smallest, only 62.3mV dec -1 , indicating that the OER reaction kinetics of this material is faster. Figure 6 (d) is the EIS (electrochemical impedance spectroscopy) test analysis diagram of different catalysts. It can be seen that the charge transfer resistance (Rct) of the Cl-modified CoMnP material is the smallest, indicating that Cl modification can improve the conductivity and electron transfer ability of bimetallic phosphides to a certain extent. Figure 6 (e) is the stability test curve of CoMnP-Cl under constant current. It can be seen that the material is stable at 100 mA cm -2 It can operate stably for 500 hours at a current density of 100 nm with minimal voltage change.
[0077] The electrochemical activities of different catalysts were analyzed by first measuring cyclic voltammetry (CV) curves at different scan rates in the non-Faraday region, calculating the double-layer capacitance (Cdl), and then estimating the electrochemically active specific surface area (ECSA). Figure 7 The chlorine-modified bimetallic phosphide prepared in Example 1, the fluorine-modified bimetallic phosphide prepared in Example 2, the bromine-modified bimetallic phosphide prepared in Example 3, the iodine-modified bimetallic phosphide prepared in Example 4 and the bimetallic phosphide sample prepared in Comparative Example 1 were subjected to the following scanning rates: 20, 40, 60, 80, 100 and 120 mV s -1 The CV curve when Figure 8 (a) is a curve fitting the capacitance current and scan rate of the electrode. Figure 8 (b) is the LSV curve after normalization of electrochemical active surface area. Figure 7 , Figure 8 It can be seen that the CoMnP-Cl electrode has the highest double layer capacitance of 58.9 μF cm -2 The CoMnP-Br electrode was second (41.5 μF cm -2), which is much higher than that of CoMnP electrode (15.5 μF cm -2 ), CoMnP-F electrode (2.1 μF cm -2 ), and CoMnP-I electrodes (7.6 μF cm -2 ), which proves that halogen Cl-modified and Br-modified CoMnP can increase the electrochemical specific surface area to a certain extent, obtain more OER catalytic active reaction sites, and facilitate efficient catalytic reactions of the catalyst; the Cl-modified CoMnP still has excellent catalytic performance after normalization treatment, indicating that the addition of halogen Cl fundamentally improves the OER catalytic activity, proving the feasibility of the halogen modification strategy for improving transition metal phosphides.
[0078] Test Example 5
[0079] This test is used to illustrate the HER performance and stability of the halogen-modified bimetallic phosphide material of the present invention.
[0080] The same operation as above was used to test and analyze the HER catalytic performance of the samples. CoMnP catalysts modified with different halogens were assembled in a three-electrode system at room temperature. The HER performance and stability were also tested in an alkaline environment (1M KOH). Comprehensive analysis of the test results showed that the HER catalytic performance of cobalt manganese phosphide can be significantly improved after modification with chlorine and bromine. The specific results are as follows:
[0081] Linear sweep voltammetry (LSV) tests were performed on different catalysts. The test results are shown in Figure 2. Figure 9 As shown in (a), compared with fluorine and iodine modifications, Cl and Br modified CoMnP exhibited excellent HER catalytic performance, among which: Cl modified CoMnP showed the best HER catalytic performance at 10 mA cm -2 The overpotential is only 51mV at a current density of 1000 nm, which is better than that of commercial catalyst Pt / C (184mV@10mA cm -2 ). Figure 9 (b) Different current densities (10, 100 and 300 mA cm -2 ) under different overpotentials of catalysts. It can be seen that the Cl-modified CoMnP material has a high overpotential at 300 mA cm -2 It also has a low overpotential of only 192 mV at a larger current density, followed by Br-modified CoMnP. Figure 9 (c) is the Tafel slope of different catalysts. It can be seen that the Tafel slope of Cl-modified CoMnP material is the smallest, only 68.7mV dec -1 The results show that the HER reaction kinetics of Cl- and Br-modified CoMnP materials are faster. Figure 9(d) is the EIS (electrochemical impedance spectroscopy) test analysis diagram of different catalysts. It can be seen that the charge transfer resistance (Rct) of Cl-modified CoMnP material is the smallest, followed by Br-modified CoMnP. Figure 9 (e) is the stability test curve of CoMnP-Cl under constant current. It can be seen that the material is stable at 10 mA cm -2 It can operate stably for 550 hours at a current density of 100 nm.
[0082] The electrochemical activities of different catalysts were also analyzed. First, the cyclic voltammetry (CV) curves at different scan rates in the non-Faraday region were tested, the double-layer capacitance (Cdl) was calculated, and then the electrochemically active specific surface area (ECSA) was estimated. Figure 10 (ae) The halogen-modified bimetallic phosphide samples prepared in Examples 1-4 and the bimetallic phosphide sample prepared in Comparative Example 1 were analyzed at scan rates of 20, 40, 60, 80, 100, and 120 mV s -1 The CV curve when Figure 11 (a) is a curve fitting the capacitance current and scan rate of the electrode. Figure 11 (b) is the LSV curve after normalization of electrochemical active surface area. Figure 10 ,11 It can be seen that the CoMnP-Cl electrode has the highest double layer capacitance of 66μFcm -2 , CoMnP-Br electrode (64 μF cm -2 ), which is much higher than that of CoMnP electrode (47 μF cm -2 ), CoMnP-F electrode (6 μF cm -2 ) and CoMnP-I electrodes (30 μFcm -2 ), which proves that the modification of CoMnP by halogen Cl or Br can increase the electrochemical specific surface area to a certain extent, obtain more HER catalytic active reaction sites, and is conducive to the efficient catalytic reaction of the catalyst; the Cl or Br modified CoMnP still has excellent catalytic performance after normalization treatment, indicating that the incorporation of halogen Cl or Br fundamentally improves the HER catalytic activity.
[0083] Test Example 6
[0084] This test is used to illustrate the electrocatalytic water splitting performance of the Cl-modified bimetallic phosphide material of Example 1 of the present invention.
[0085] First, different catalysts were assembled in a two-electrode system to test their catalytic performance in water splitting. Figure 12 (a) LSV curves of complete water splitting of different catalysts in alkaline electrolyte (1 M KOH); Figure 12(b) is the LSV curve of the complete water splitting of CoMnP-Cl in alkaline seawater electrolyte (1 M KOH + seawater); Figure 12 (c) is the stability test curve of CoMnP-Cl under constant current density. Figure 12 (a) It can be seen that Cl-modified CoMnP exhibits excellent overall water splitting performance, reaching 10 mA cm in 1 M KOH alkaline electrolyte. -2 The current density requires a battery voltage of 1.51V.
[0086] Test Example 7
[0087] Application of Cl-modified bimetallic phosphide materials prepared on different nickel substrates in AEM electrolytic cells. Figure 13 As shown in the figure, the Cl-modified bimetallic phosphide materials prepared on different nickel substrates have excellent performance in the AEM electrolytic cell. The nickel felt substrate has the best full water splitting performance, reaching 1000 mA cm -2 The high current density only requires a battery voltage of 2.08V, such as Figure 14 As shown in the figure, the catalyst was assembled into an AEM electrolyzer to achieve continuous water decomposition under industrial conditions. The catalyst was able to operate stably for 800 hours and has great development prospects as a bifunctional electrocatalyst.
[0088] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art who, within the technical scope disclosed by the present invention, makes equivalent substitutions or changes based on the technical solutions and improved concepts of the present invention shall be covered by the scope of protection of the present invention.
Claims
1. A halogen-modified bimetallic phosphide, characterized in that: The invention comprises a nickel substrate and a halogen-modified bimetallic phosphide grown on the nickel substrate, which is doped with halogen, wherein the halogen is chlorine or bromine, and contains phosphide of metal cobalt and nickel, and has metal cobalt and manganese as well as bonding of phosphorus and oxygen.
2. The halogen-modified bimetallic phosphide according to claim 1, characterized in that: The chlorine-modified bimetallic phosphide CoMnP-Cl is a nanoflower structure obtained by rotating a nanorod with a tapered tip, and is evenly and densely distributed on a nickel substrate.
3. The halogen-modified bimetallic phosphide according to claim 2, characterized in that: The diameter of the nanorods in the chlorine-modified bimetallic phosphide CoMnP-Cl is 80-300 nm, and the surface of the nanorods is smooth.
4. The halogen-modified bimetallic phosphide according to claim 1, characterized in that: The bromine-modified bimetallic phosphide CoMnP-Br is a nano-spherical structure composed of nano-rods.
5. The halogen-modified bimetallic phosphide according to claim 1, characterized in that: The nickel substrate comprises foamed nickel, nickel mesh and nickel felt; the halogen doping amount is 0.1-1wt%.
6. A method for preparing a halogen-modified bimetallic phosphide, characterized in that: A nickel base material is pretreated as a base, and a cobalt source material and a manganese source material are used to carry out a hydrothermal reaction in the presence of NH4X, where X is Cl or Br, and (NH2)2CO to deposit a halogen-modified cobalt-manganese precursor on the base; a halogen-modified bimetallic phosphide is prepared by a high-temperature phosphating method using NaH2PO2.
7. The preparation method according to claim 5, characterized in that: The temperature of the hydrothermal reaction is 100-200°C and the time is 4-20 hours; The high temperature phosphating method is as follows: placing the halogen-modified cobalt-manganese precursor in the downstream position of a tubular furnace, placing NaH2PO2 in the upstream position of the tubular furnace, and calcining in an inert atmosphere to prepare a halogen-modified bimetallic phosphide.
8. The preparation method according to claim 7, characterized in that: The calcination temperature is 300-450° C. and the calcination time is 0.5-3 hours.
9. Use of the halogen-modified bimetallic phosphide according to claim 1 in electrocatalytic oxygen evolution and / or electrocatalytic hydrogen evolution.
10. Use of the halogen-modified bimetallic phosphide according to claim 1 in electrocatalytic water splitting.